Shelf life and quality of minimally processed pet foods and pet food ingredients - Haverkamp, Megan Elizabeth Morts (Kansas State University, 2020)
Pet food sales in the US have increased at a 5.1% annual rate since 2015 (Packaged Facts, 2020) to an estimated $54.62 billion in 2019. Much of this growth has been due to new food forms and ingredients. The fastest growing categories have been raw-frozen and freeze-dried foods. Further, new minimally processed animal proteins and plant proteins have been introduced. Raw-frozen and freeze-dried pet foods contain a large proportion of high fat meats which increases the chance for oxidation. Further, many of the new minimally processed protein sources and alternative ingredients such as legumes have not been evaluated for their nutritional contribution. The link is processing and how it influences the nutritional quality of these two foundations of essential nutrients for pets. The objective therefore is to determine the impact process has on oxidation of fats in these new food forms and the quality of protein in these novel ingredients. Two experiments were conducted to determine the impact of increased storage time on raw-frozen and freeze-dried pet food patties based on chicken or lamb. Raw-frozen samples were stored at -20°C 0, 4, 8 or 16 weeks. Freeze-dried samples were stored frozen for 12, 24, and 36 weeks prior to freeze drying and then stored dried for an additional 4, 8, 16 weeks. Raw-frozen chicken and lamb patties had increased peroxide value (PV) as storage time increased (P < 0.05). Propanal content was higher in both raw-frozen chicken and lamb at 4 and 8 weeks of storage but at 16 weeks was not different from week 0 (P < 0.05). Freeze-dried samples had reduced PV during storage and increased free fatty acid and propanal concentration (P < 0.05). Among antioxidants, mixed tocopherols provided more protection against oxidation compared to other treatments (P < 0.05). Two 10-day chick growth assays were conducted to determine protein efficiency ratio (PER) of various proteins differing in process and source. Spray dried egg (SDEG) was considered the reference in both experiments and resulted in the highest PER values (P < 0.05). Rendered protein meals, dehydrated chicken, and two spray dried chicken powders were evaluated in experiment one. The dehydrated chicken and the high protein chicken powder had similar PER values to SDEG. The rendered protein meals had lower PER values compared to the gently processed meats and SDEG (P < 0.05). Protein digestibility amino acids scores (PDCAAs) were determined in experiment one and were highly correlated to PER (R=0.80 for dog and R=0.95 for cat; P<0.05). In experiment two, the PER of all legume sources were lower than SDEG (P < 0.05). When legume sources were mixed with SDEG, there was an improvement in PER but not enough to match SDEG. Overall, these experiments provide supporting information regarding lipid and protein changes due to process and storage. Fat and protein are the two primary vehicles for the delivery of required nutrients to pet foods and the process can have a deleterious effect on their availability. Decreasing processing temperatures and providing preservative antioxidants may benefit nutrient retention in modern processed foods.
Keywords: Petfood; Oxidation; Shelf-life; Protein; Quality